Uke, flow and Rock'n'Roll. Issue 2 (1st August 2019) - Reese, Jill Alyse
Community ukulele groups' fertile contexts for participatory and amateur musicking are increasing in popularity. Though researchers have begun to describe contexts for community ukulele groups, more research is necessary to understand participants' perceptions of their lived-experiences within the space of the jam sessions. Therefore, the purpose of this phenomenological case study is to describe the lived experiences of adults participating in a community ukulele group. Several research questions guided this study. First, what do they experience during jam sessions, and how do they describe their experiences? Second, how do these experiences relate to their sense of musical self? Third, what mechanisms impact their perceptions of their experiences? Three distinct but related ideas constitute the theoretical framework for this study: Turino's concept of participatory performance, Csikszentmihaly's flow theory, and Turner's concept of communitas. Data were individual interviews and small-group re-enactment interviews with eleven community ukulele participants. The essence of the experience was that liminal space emerged in the context of the jam sessions and supported communitas that resulted in temporary transformation of identity and transcendence of concerns. This essence was supported by three themes: characteristics of liminal space, manifestations of communitas, and transformation and transcendence.